(untitled) - Vander, Arthur J. (New York, 1985)
The new edition of this physiology text has been written to teach the functions of the human body from a mechanistic approach, and it stresses homeostatic and control systems. The mechanistic approach explains physiology as a dynamic process of chains of causal links rather than just stating facts and events. The sections on signal transduction mechanisms have been simplified, to emphasize the basic principles. Each chapter contains colour-coded flow charts which review the important material, and there are also an increased number of summary tables. The coverage of exercise physiology has been revised, as have the sections on genetics: these now include the human genome project, transcription factors and gene cloning.
Dinh dưỡng cộng đồng
Keywords: Human physiology,Physiology,Sinh lý con người,Sinh lý học